Methotrexate as an Adjuvant in Severe Thyroid Eye Disease: Does It Really Work as a Steroid-Sparing Agent?. Issue 4 (July 2019) - Yong, Kai-Ling; Chng, Chiaw-Ling; Ming Sie, Nicole; Lang, Stephanie; Yang, Morgan; Looi, Audrey; Choo, Chai-Teck; Shen, Sunny; Seah, Lay Leng
Abstract : Purpose: To compare the efficacy and safety of adjunctive oral methotrexate with intravenous pulsed methylprednisolone against methylprednisolone alone in the treatment of severe thyroid eye disease. Methods: Retrospective review of clinical data of patients with severe sight-threatening thyroid eye disease with compressive optic neuropathy treated with methylprednisolone with and without methotrexate. Eye disease outcome measures (e.g., VISA inflammatory score and vision) at 0, 3, 6, 12, and 18 months were recorded. Results: There were 72 subjects including 33 who had methylprednisolone alone and 39 with methylprednisolone with methotrexate. There were no statistical differences in demographics and baseline measures of disease activity or vision between the 2 treatment groups. No significant statistical differences in the cumulative dosage of methylprednisolone or occurrence of restrictive myopathy, raised intraocular pressure, proptosis, and exposure keratopathy between the groups at 0, 3, 6, 12, and 18 months were found. However, subjects who received methylprednisolone with methotrexate had better visual acuity of more than 2 lines on Snellen chart ( p = 0.026) and VISA inflammatory score ( p = 0.034) at 3 months, but no differences at 6, 12, and 18 months. Three patients who received methylprednisolone with methotrexate had transient worsening of liver function. No patient developed severe adverse reaction. Conclusions: The results demonstrated improved vision and disease activity at 3 months in the combination treatment group. This may suggest that the addition of methotrexate to methylprednisolone is beneficial for accelerating suppression of disease activity and hastens visual recovery. Addition of methotrexate to methylprednisolone did not reduce the requirement for steroids. Abstract : Use of adjuvant methotrexate for severe thyroid eye disease improved vision and inflammatory scores at 3 months, but no reduction in steroid requirement. The authors recommend its use for hastening visual recovery and accelerating inflammatory suppression.Supplemental Digital Content is available in the text.